Syed Muhammad Naquib Al-Attas' Critical Thinking Towards The Structure Of Western Scientific Epistemology - Tohedi Tohedi (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
The dominance of secular Western epistemology and its uncritical adoption by some Muslim scholars have created a dichotomy of knowledge that challenges the integration of Islamic metaphysical values into contemporary educational and intellectual discourse. Syed Muhammad Naquib al-Attas is part of the group of critical Islamic thinkers and proposed the discourse of the Islamization of knowledge, which was first carried out at a conference in Mecca in 1977. The emergence of the Islamization of knowledge was a response to the disappointment of some Islamic thinkers towards Western dominance, which tended to be secularistic-materialistic, causing Muslims to experience both internal and external pressures in terms of thought as well as arrogant attitudes. Then they initiated and held a collective meeting to discuss the Islamization of knowledge, attended by the Muslim world in Mecca. This Islamization of knowledge also provided space to bring together religious sciences and natural sciences, or to reconcile religion with knowledge based on religion. Thus, it was an intellectual response to the negative impact of Western modern science, which was increasingly apparent and felt by the people of the world as a consequence of the crisis in the capabilities of modern science. Thus, this writing uses the discourse analysis method with a descriptive-critical approach. However, in addition to that, the author also reveals Naquib al-Attas's way of thinking in discussing the domination of Western epistemology over Islam, namely the historical fusion of secular Western thought from the Greek, Modern, and contemporary eras, which is not in accordance with Islamic epistemology.